The Relationship Between Online communication aspects and Personality Traits - Dudkina, Aija; Barkane, Elīna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This reference The relationship between online communications aspects and Personality Traits theoretical backround contains a review of best-known and the most actual theories about the online communications aspects and personality traits. Aim of the research is theoretical basis and practical research to investigate whether there is a relationship between online communication aspects and personality traits. Terms of Reference: 1st to analyze and summarize the theoretical literature on communication aspects online theories of personality factors. 2nd select a research methodology. Methods of the research: Survey BFI and the research author’s constructed a questionnaire. Respondents of the research: together 82 users of social networks like draugiem.lv and facebook.com. During the research the proved that there is a relationship between the individuals five personality factors: openness, conscientiousness, extraversion, agreeableness, neuroticism, and some units (variables) of online self-presentetation through profile image.